Science under Fire. - Martin, Joseph D. (History Today, 2025)
The article focuses on the significant impact of the dismissal of Dr. A.V. Astin, director of the US National Bureau of Standards (NBS), on the American scientific community in 1953. Astin was ousted after the NBS deemed the car battery additive AD-X2 ineffective, a decision that conflicted with the interests of Sinclair Weeks, the new Secretary of Commerce, who sought to support small businesses. The scientific community reacted strongly, with over 12 organizations publicly condemning the dismissal and advocating for the autonomy of scientific institutions. Ultimately, Astin was reinstated pending a review, which reinforced the principle that only the scientific community should govern its standards and practices, a lesson that remains relevant in contemporary discussions about the independence of scientific institutions in the US.